2012
DOI: 10.21608/jssae.2012.54707
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Organic Manuring and Mineral Fertilization for Wheat Yield and Its Components in El-Dakahlia Governorate .

Abstract: A factorial field experiment on wheat crop was conducted during two successive growth seasons of (2009/2010) ; (2010/2011) as two different On-farm trials sited in El-Dakahlia Governorate. The factors involved organic manuring from two biological treating composts of rates (0, 10 and 20 m 3 .fed-1) and NPKZn-mineral fertilization of the optimum recommended rates. The two experimental sites were clayey in texture have the average values of salinity index ECe = 3.8 dS.m-1 ; pH = 7.8 and the available soil forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The application of organic residues and biofertilizers are considered as promising practices of improving the nutritive and productive capacities of such soils either directly or indirectly (El-Sirafy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The application of organic residues and biofertilizers are considered as promising practices of improving the nutritive and productive capacities of such soils either directly or indirectly (El-Sirafy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Pfertilization from (calcium super phosphate source) reacts as source of Ca ++ for replacing Na + in such soils (Genaidy, 2011). Also, El-Sirafy et al, (2012) showed that wheat yield components have been increased by applying organic manure, bio-treated compost along with N, P, K and Zn mineral fertilization. So the objective of this presented research is to indicate the main effects of organic fertilization rates (as compost) and phosphorus fertilization (as calcium super phosphate) as well as interaction effects on wheat yield, wheat grains -N, P concentrations and protein content in slightly salt-affected soils.…”
Section: Introdctionmentioning
confidence: 99%